The training of the Science teachers - Climent I Giner, Daniel (Avances en Supervisión Educativa, 2006)
The curricular contents taught to students in the Natural Science lessons during their Secondary Education should be helpful to understand Nature, its relationships, and the whole world from scientific principles and a critical attitude, far from any kind of dogmatism, especially those next to fanatic and hyper-religious positions. The curricular contents must be established and taught to students by teachers who are efficient, experienced and professionally successful.The fact of the matter is that curricula are selected either by university dons, publishing houses managers or theoretitians, all of them very distant from the teaching profession. Therefore, the contents are often too abstract, badly scheduled, misleading and even false. The problems do not lie only on the curricula taught, some other elements are questioned such as the academic qualifications of teachers in Primary and Secondary Education, the procedure to select teachers and the quality of practising teachers' performance.